Control of complex weed flora in direct seeded rice using bispyribac-sodium in combination with other herbicides - Khippal, Anil; Singh, Jasbir; Chhokar, Rajender Singh (Journal of Cereal Research, 2025)
Field experiments were conducted to identify the suitable chemical weed control options in direct seeded rice (DSR) with farmers’ participatory research mode at Amrik Farm, Hajwana (Kaithal, Haryana, India) during kharif seasons of 2012, 2013 and 2014. The weed control treatments included bispyribac sodium at 25 g ha-1, pendimethalin at 1.0 Kg ha-1, pendimethalin at 1.0 Kg ha-1 followed by (fb) bispyribac sodium 25 g ha-1 + pyrazosulfuron 25 g ha-1, ethoxysulfuron at 18.75 g ha-1, bispyribac sodium at 25 g ha-1 fb ethoxysulfuron 18.75 g ha-1, weedy and weed free check. The major weeds present in experimental plots consisted of grasses (Dactyloctenium aegyptium, Echinochloa colona, Echinochloa crus-galli, Leptochloa chinensis), sedges (Cyperus difformis, Cyperus rotundus, Fimbristylis miliacea) and broad-leaved (Trianthema portulacastrum, Ammannia bacciferra, Digera arvensis, Eclipta prostrata, and Phyllanthus niruri) weeds. Among herbicide treatments, maximum effective tillers (387 m-2), panicle length (23.6 cm), grains per panicle (76.7), thousand grain weight (22.57 g) and grain yield (3794 Kg ha-1), were recorded with application of pendimethalin at 1.0 Kg ha-1 fb bispyribac sodium 25 g ha-1 + pyrazosulfuron 25 g ha-1 and this treatment was statistically at par to weed free conditions. The uncontrolled weed competition caused an average 74.3 per cent grain yield reduction as compared to weed free environment. Among herbicides treatments, weed control efficiency (91.8 %), weed control index (88.0 %) and herbicide efficiency index (23.65%) were highest when pendimethalin at 1.0 Kg ha-1 fb bispyribac sodium 25 g ha-1 + pyrazosulfuron 25 g ha-1 were applied to control weeds whereas; weed index (1.20 %) was lowest in this treatment. DOI: http://doi.org/10.25174/2249-4065/2019/97078